The effects of mining operations in community development : case study of Mogalakwena Mine in the Limpopo Province, South Africa - Hlungwane, Rosalia Given (My University, 2025)
Mining operations are a necessity to the economic growth of the country as they bring about changes and deal with the triple challenges of poverty, unemployment, and inequality. Host communities and the country get employment opportunities, infrastructure development, contribution towards the GDP of the country, better education, investment, and better life for host communities. However, mining operations takes place in areas inhibited by the people and in the process, even though there’s policies and legislations for mining operations, people tend to suffer from resettlement and the negative effects that the mine has on local people. The negative effects include house damages caused by mine blasting, health issues caused by pollution, inadequate infrastructure development, underground water pollution etc. Thus, the study argues that mining operations affects the resettled and host communities more negatively than they do positively, and mining operations prioritises profit more than the protection of community development of the host communities and other benefits. The study thus has the findings that mining operations have more negative effects than positive, and the development of host communities is not prioritised. The study therefore recommend that there must be meaningful and extensive public participation of the host communities in the development of Social and Labour Plans (SLPs) and the entire mining process, including their basic needs and problems be prioritised. This study adopted the interpretivist paradigm as it is based on exploring social reality, understanding of human behaviour and will contribute to finding solutions to a social problem through reasoning and observation. This study also adopted mixed method research using a descriptive enquiry in order to produce better results and obtain a deeper understanding of the effects of mining operations on the development of host communities
Thesis (M.Dev. (Planning and Management)) -- University of Limpopo, 2025
Keywords: South Africa; Social & labour plans; Rural livelihoods; Mining operations; Community development; Mines and mineral resources; Mine safety; Mineral industries